Functionalized wood as bio-based advanced materials: Properties, applications, and challenges. (April 2022) - Beims, Ramon Filipe; Arredondo, Rosa; Sosa Carrero, Dennise Johanna; Yuan, Zhongshun; Li, Hongwei; Shui, Hengfu; Zhang, Yongsheng; Leitch, Mathew; Xu, Chunbao Charles
Abstract: Due to millions of years of natural evolution, wood has a unique structure that has inspired many researchers to use it as a template to create bio-based advanced materials for various applications. Apart from being a renewable and sustainable source of energy and materials, such as pulp and paper, the wood structure can be functionalized through different methodologies to be applied as advanced materials for water filtration and purification, structural engineering, energy storage, and energy-efficient buildings. The renewable aspect is an intrinsic advantage to wood-based advanced materials; however, this is not the only attribute necessary for the commercial development of novel materials: their properties must reach the minimum requirements of the target applications. In this review, the properties of functionalized wood materials are compared with those of other conventional and emerging synthetic materials, and their potential in various applications as advanced materials is analyzed. Furthermore, challenges with sustainability, feasibility, and preparation of functionalized wood are discussed, suggesting a need for the future development of these novel bio-based advanced materials. Highlights: Methods for functionalized wood manufacture are introduced. Potential applications of functionalized wood are presented. Properties are compared with those of conventional or emerging synthetic materials. Sustainability, feasibility, and challenges of the preparation process are discussed.